Temporary placement of fully covered self-expandable metal stents in biliary complications after liver transplantation - Sauer, P.; Chahoud, F.; Gotthardt, D.; Stremmel, W.; Weiss, K.-H.; Büchler, M.; Schemmer, P.; Weitz, J.; Schaible, A. (Endoscopy, 2012)
In the present study we prospectively evaluated the safety and efficacy of temporary fully covered, self-expandable metal stents (fcSEMS) to treat biliary strictures (n = 9), leaks (n = 9), and combined lesions (n = 1) occurring after liver transplantation, when standard endoscopic attempts had failed. Placement of fcSEMS and their removal in scheduled patients were successful and without complications. Resolution of the biliary lesion was confirmed in 15 of 19 patients (79 %). Treatment was not successful in two patients and not evaluable in 2 other patients. Complications occurred in 9 /19 patients (47 %): stent migration in 6, stent occlusion in 1, and de novo stricture after successful treatment of a biliary leak in 2. After a median follow-up of 12 months, one recurrent anastomotic stricture was noted. Temporary placement of fcSEMS in biliary strictures and leaks after liver transplantation provides satisfactory results even in patients who have undergone multiple previous conventional endoscopic attempts, and offers an alternative approach to surgical intervention.